On the structure and function of Sorghum bicolor CHIP (carboxyl terminus of Hsc70-interacting protein): A link between chaperone and proteasome systems. (July 2020) - Gonçalves, Conrado de C.; Pinheiro, Glaucia M.S.; Dahlström, Käthe M.; Souto, Dênio E.P.; Kubota, Lauro T.; Barbosa, Leandro R.S.; Ramos, Carlos H.I.
Graphical abstract: Highlights: SbCHIP is a non-spherical symmetric dimer in solution. SbCHIP forms complexes with Hsp70 and Hsp90 from plant and interacts with E2 enzymes UbcH5 and UbcH13. SbCHIP is able of autoubiquitination, but in the presence of substrate SbCHIP ubiquitinates Hsp70, Hsp90 and luciferase. Abstract: The co-chaperone CHIP (carboxy terminus of Hsc70 interacting protein) is very important for many cell activities since it regulates the ubiquitination of substrates targeted for proteasomal degradation. However, information on the structure-function relationship of CHIP from plants and how it interacts and ubiquitinates other plant chaperones is still needed. For that, the CHIP ortholog from Sorghum bicolor (SbCHIP) was identified and studied in detail. SbCHIP was purified and produced folded and pure, being capable of keeping its structural conformation up to 42 °C, indicating that cellular function is maintained even in a hot environment. Also, SbCHIP was able to bind plant Hsp70 and Hsp90 with high affinity and interact with E2 enzymes, performing E3 ligase activity. The data allowed to reveal the pattern of plant Hsp70 and Hsp90 ubiquitination and described which plant E2 enzymes are likely involved in SbCHIP-mediated ubiquitination. Aditionally, we obtained information on the SbCHIP conformation, showing that it is a non-globular symmetric dimer and allowing to put forward a model for the interaction of SbCHIP with chaperones and E2 enzymes that suggests a mechanism of ubiquitination. Altogether, the results presented here are useful additions to the study of protein folding and degradation in plants.